Islam di “Negeri Bawah Angin” dalam Masa Perdagangan - Azyumardi Azra (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
This article is a review of the book Anthony Reid, Southeast Asia in the Age of Commerce 1450-1680, Volume One: The Lands below the Winds, New Haven & London: Yale University Press, 1988; Southeast Asia in the Age of Commerce 1450-1680, Volume Two: Expansion and Crisis, New Haven & London, Yale University Press, 1993.Studies of 'The Lands Below the Winds' - a medical Middle Eastern term reffering to Southeast Asia - especially those related to Islam, remain incomplete. Numerous problems, subject and topics are still hotly debated among schoolars of Southeast Asia. Also, there are many issues which need more adequate and serious research.DOI: 10.15408/sdi.v3i2.811